The Causes of Students Bullying - Ramadhani, Sunainatul; Lestari, Putri Ayu; Emelda, Emelda; Norhayatun, Norhayatun (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research aims to open up the public's view that perpetrators of bullying also need to receive special attention, not just be judged and considered completely wrong. One of the main factors in bullying occurs due to a lack of concern from the surrounding environment. By using a qualitative approach through source triangulation method towards students who bully at MTS Nurul Ummah, and those closest to them. The research results show that internal and external factors are the biggest causes of bullying. This lack of concern extends to perpetrators who want to be seen and be the center of attention. This research recommends handling bullying perpetrators by not judging the perpetrators, providing a form of concern for the perpetrators, and providing a sense of responsibility to the perpetrators so that the perpetrators can learn from healthy experiences.